Three-year study of health care-associated infections in a Turkish pediatric ward - ALTINKANAT GELMEZ, GÜLŞEN (J INFECTION DEVELOPING COUNTRIES, 2014)
Introduction: Health care-associated infections (HCAIs) can cause an increase in morbidity, mortality and costs, especially in developing countries. As information on the epidemiology of HCAIs in pediatric patientsinTurkey is limited, we decided to study the annual incidence and antibiotic resistance patterns in our pediatric ward at Marmara University Hospital. Methodology: All hospitalized patients in the pediatric ward were assessed with regard to HCAIs betweenJanuary 1, 2008 and December 31, 2010. Data was prospectively collected according to standard protocols of the National Nosocomial Infections Surveillance System (NosoLINE). Results: A total of 16.5% of all hospitalized patients developed HCAIs in the three years studied. The most frequent HCAIs were urinary tract infections (UTI) (29.3%), bloodstream infections (27%) and pneumonias (21%). While the most frequent agent isolatedfrom UTI was Escherichia coli (26%), the most common agent in blood stream infections was Staphylococcus epidermidis (30.4%). Vancomycin resistance was found in 73.3% of all Enterococcus faecium strains. Extended-spectrum beta-lactamase was detected in 58.3% of Klebsiella pneumoniae and E. coli isolates. Conclusions: Continual HCAI surveillance is important to determineits rate. Knowledge of the HCAI incidence can influence people's use of broad-spectrum antibiotics and encourage antibiotic rotation. Moreover, the knowledge of HCAI incidence may support the infection control programmes, including education and isolation methods which ultimately may help to reducethe rate of the HCAIs.
Keywords: health care-associated infections; pediatric unit; surveillance; nosocomial infections; children; BLOOD-STREAM INFECTIONS; NOSOCOMIAL INFECTIONS; RISK-FACTORS; HOSPITALS; EPIDEMIOLOGY